RM AOI Algorithm Development of FPCB Bending for Zero Bezel Flexible OLED - Kyunghan Chun (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, we propose an RM(radius measurement) AOI(automatic optical inspection) method to determine the suitability of the FPCB(flexible printed circuit board) bending process for zero bezel OLED(organic light emitting diode). Recently, OLED has become the mainstream of mobile displays, and it is possible to realize a flexible display that can flexibly bend the screen. In particular, in order to increase the size of these displays, the zero bezel technology that reduces the bezel as much as possible is attracting attention. Mass production and quality uniformity are required through AOI inspection after bending. We develop an algorithm for RM AOI, apply non-linear optimization to improve inspection performance, and verify through experiments